PENGENALAN LITERASI KEUANGAN DAN PERSONAL BRANDING DI ERA DIGITAL BAGI GENERASI Z DI SMK PGRI 1 KEDONDONG - Dhiona Ayu Nani; Larasati Ahluwalia; Dian Novita (Universitas Teknokrat Indonesia, 2021)
Research conducted by Kredivo and Katadata in 2020, generation Z and Millennials contributed 85% of total transactions. Furthermore, the government is currently focusing on recovering the national economy, which has fallen due to the ongoing Covid-19 pandemic. Generation Z, which is expected to become a demographic bonus for the workforce in the next few years, should be equipped with financial literacy and personal branding in order to survive and compete with the environment. This Community Service is carried out with the aim of providing an understanding of financial literacy and personal branding. As previously discussed, Generation Z needs to be equipped with financial literacy so that later they can be financially independent. In addition, students can develop themselves through personal branding that utilizes digital business platforms.Keywords: Generation Z, Millennials, National Economy, Financial Literacy, Personal Branding